2020
DOI: 10.1371/journal.pbio.3000852
|View full text |Cite
|
Sign up to set email alerts
|

Centrioles are amplified in cycling progenitors of olfactory sensory neurons

Abstract: Olfaction in most animals is mediated by neurons bearing cilia that are accessible to the environment. Olfactory sensory neurons (OSNs) in chordates usually have multiple cilia, each with a centriole at its base. OSNs differentiate from stem cells in the olfactory epithelium, and how the epithelium generates cells with many centrioles is not yet understood. We show that centrioles are amplified via centriole rosette formation in both embryonic development and turnover of the olfactory epithelium in adult mice,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 39 publications
(61 reference statements)
4
27
0
Order By: Relevance
“…To better visualize centriole migration in OSNs at higher resolution we applied expansion microscopy (Gambarotto et al, 2019, Sahabandu et al, 2019 to sections of adult olfactory epithelium. We were able to reproducibly expand these samples approximately 4-fold, and could resolve olfactory cilia in mature OSNs, as well as migrating centrioles in immature OSNs (Fig These results suggest that progenitor cells form the majority of centrioles present in the dendritic knob of mature OSNs, in keeping with our previously published work (Ching & Stearns 2020).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…To better visualize centriole migration in OSNs at higher resolution we applied expansion microscopy (Gambarotto et al, 2019, Sahabandu et al, 2019 to sections of adult olfactory epithelium. We were able to reproducibly expand these samples approximately 4-fold, and could resolve olfactory cilia in mature OSNs, as well as migrating centrioles in immature OSNs (Fig These results suggest that progenitor cells form the majority of centrioles present in the dendritic knob of mature OSNs, in keeping with our previously published work (Ching & Stearns 2020).…”
Section: Resultssupporting
confidence: 86%
“…Newly formed centrioles are attached to their associated mother centriole by an engagement linker, which is broken by passage through mitosis, and disengaged centrioles are linked by cohesion fibers. Our inability to resolve centriole-centriole relationships in the migrating groups due to tight packing within the narrow dendrite prevents us from being able to determine whether the engagement link is responsible for their grouping; however, we consider it unlikely that all centrioles are held together this way, based on our previous results showing that centriole amplification is initiated prior to mitotic divisions in progenitors (Ching & Stearns, 2020).…”
Section: Groups Of Osn Centrioles Migrate From the Basal Lamina To The Apical Surface In Tandem With Dendrite Outgrowthmentioning
confidence: 99%
“…Recent studies have shown that, although deuterosomes might initially assemble in close proximity to the preexisting centrioles within the cell (Al Jord et al 2014), these structures are not required for deuterosome assembly (Mercey et al 2019a(Mercey et al , 2019bZhao et al 2019) (Figure 2c). Nevertheless, preexisting centrioles can be used as platforms for centriole amplification (Ching & Stearns 2020, Mercey et al 2019b) (Figure 2c). Indeed, in the absence of both centrioles and deuterosomes, the correct centriole number assembles from a microtubule-convergence area containing PCM proteins (Mercey et al 2019a(Mercey et al , 2019b) (Figure 2a).…”
Section: Centriole Birth and Self-assemblymentioning
confidence: 99%
“…These processes might be differently regulated in differentiated tissues. For example, in the progenitor cells of mouse olfactory neurons, extra centrioles are assembled prior to multiciliation and cell division in rosette-like structures (Figure 2c) associated with increases in Plk4 and STIL transcript levels (Ching & Stearns 2020). It would be interesting to understand if mouse olfactory neuron progenitors can either suppress or cope with these defects, or if cells that acquire karyotypic errors are selected against.…”
Section: Centrosome Changes During Developmentmentioning
confidence: 99%
“…This is independent of the mode of centriole biogenesis, duplication or de novo. Indeed, it has been observed that both the mean and the variance increase in systems where extra centrioles are produced, such as olfactory neuron progenitors [48], where overproduction occurs via rosettes, and other multicilliated cells, where overproduction occurs at deuterosomes or de novo [49][50][51][52]. In all these cases, the extra centrioles are associated with Plk4 and STIL overexpression, which could lead to an increase in centrosomal SAS-6 influx.…”
Section: Generality and Relation To Other Modelsmentioning
confidence: 99%